1987
DOI: 10.1093/infdis/155.2.262
|View full text |Cite
|
Sign up to set email alerts
|

Serological Tests for Blastomycosis: Assessments During a Large Point-Source Outbreak in Wisconsin

Abstract: Enzyme immunoassay (EIA), immunodiffusion (ID), and complement fixation (CF) tests for antibody to the A antigen of Blastomyces dermatitidis were assessed in 47 patients in an epidemic of blastomycosis and in 89 control subjects with lower respiratory tract illness. Antibody was detected by EIA, ID, and CF in 77%, 28%, and 9% of the patients, respectively. EIA titers ranged from 1:8-1:512 (median titer, 1:128). Antibody detected by ID or CF was always detectable by EIA. Antibody was detected by EIA 13 days aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
55
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(55 citation statements)
references
References 15 publications
0
55
0
Order By: Relevance
“…Each serum specimen had been tested previously in two other studies for antibody to A antigen by enzyme immunoassay (8,13) and was tested in the present study only for antibody to WI-I by RIA. Of these sera evaluated sequentially by both tests, 82%…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each serum specimen had been tested previously in two other studies for antibody to A antigen by enzyme immunoassay (8,13) and was tested in the present study only for antibody to WI-I by RIA. Of these sera evaluated sequentially by both tests, 82%…”
Section: Resultsmentioning
confidence: 99%
“…It was The RIA we describe offers a significant advance for serological studies of blastomycosis. When results of the RIA for detection of antibody to WI-1 are compared to those reported using an enzyme immunoassay for detection of antibody to A antigen (8,13), several observations can be made: (a) antibody to WI-1 can be detected earlier, occasionally even at the onset of acute pulmonary illness; (b) antibody titers to WI-l are far higher, the GMT is -2.5 logs greater; and (c) antibody to WI-I persists for a longer interval, although antibody to both antigens declines to low or undetectable levels by 6 mo after illness onset in patients with resolution or successful treatment of disease (8). We recognize that caution should be used in drawing conclusions about the relative sensitivities of the two tests for detection of antibody in blastomycosis, since the assays were not run in parallel in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a recent review, an agar gel immunodiffusion (AGID) test showed a sensitivity of only 32%, and in previous studies less than half of blastomycosis cases were seropositive (6)(7)(8)(9)(10)(11). Complement fixation is less sensitive than AGID in patients with blastomycosis, is more difficult to perform, and offers no advantages over AGID (7)(8)(9).…”
mentioning
confidence: 99%
“…The enzyme immunoassay (EIA) is more sensitive than the AGID test, but previous tests were falsely positive in one quarter of patients with histoplasmosis (7)(8)(9)(10)(11). In one study using a commercially available EIA, the sensitivity was 100%, but false positives in nonfungal controls were detected in 20% of cases (10).…”
mentioning
confidence: 99%